The Relationship Between Family Motivation and The Role of Health Workers With Adherence to Treatment for TB Patients at Puskesmas Pagar Jati - Rahmad Gurusinga (JURNAL KEBIDANAN KESTRA (JKK), 2023)
The high incidence of TB in Indonesia is one of them caused by the lack of family motivation and the role of health workers in the healing process of TB disease, many TB sufferers do not finish treatment due to non-compliance in consuming drugs in large quantities and for a long time. TB disease if not treated immediately can have a bad impact on the sufferer himself or family around him because TB can spread quickly and can endanger health and can cause death. The purpose of this study was to see if there is a relationship between motivation and the role of health workers on adherence in treatment. The research method used a cross sectional design, data was taken by distributing questionnaires, samples of 30 people who had been determined according to research criteria, data were tested with Chi square (alpa 0.05). The test results showed that there was a relationship between family motivation and TB patient treatment adherence p value 0.00 and there was a relationship between the role of health workers and TB treatment adherence p value 0.01. It is recommended that TB sufferers must remain enthusiastic in carrying out treatment and remain obedient in taking drugs in order to achieve maximum recovery.